Razem czy osobno? Specjalizacja i integracja organów antymonopolowych, ochrony konsumentów i regulacyjnych w Polsce i krajach Unii Europejskiej - Błachucki, Mateusz (Kwartalnik Prawa Publicznego, 2017)
The article aims at analysing what is the optimal instructional design of competition agency. The main research problem concerned whether competition agencies should be solely responsible for the competition enforcement or should be multi-purpose agencies combining competition and consumer protection together with sectoral regulation. Firstly, theoretical arguments has been discussed. This allowed for identification of benefits and costs of both institutional designs. It has been followed by the analysis of actual institutional reforms that has taken place in various countries with a special attention given to justification of these reforms. Furthermore, the comparative analysis has been undertaken in order to show the institutional landscape of competition authorities in the EU countries. It was confronted with the presentation and the discussion of the Polish regulations of competition, consumer and regulatory authorities. It has been accompanied with a short presentation of the current legislative proposals regarding the institutional design of the Polish competition authority and regulators. In conclusion it has been established that there is no optimal institutional design of the competition agency that may be applicable across various jurisdiction. All arguments in favour of separation and integration should be carefully analyses against existing institutional and legal environment. Finally, the undertaken research proved that the Polish integration of competition and consumer protection within a single authority is detrimental to competition protection. Therefore, the fundamental changes to the design and the jurisdiction of the Polish competition authority are more than welcomed.